Invasion biology in non‐free‐living species: interactions between abiotic (climatic) and biotic (host availability) factors in geographical space in crayfish commensals (Ostracoda, Entocytheridae). Issue 16 (3rd December 2013) - Mestre, Alexandre; Aguilar‐Alberola, Josep A.; Baldry, David; Balkis, Husamettin; Ellis, Adam; Gil‐Delgado, Jose A.; Grabow, Karsten; Klobučar, Göran; Kouba, Antonín; Maguire, Ivana; Martens, Andreas; Mülayim, Ayşegül; et al.
Abstract: In invasion processes, both abiotic and biotic factors are considered essential, but the latter are usually disregarded when modeling the potential spread of exotic species. In the framework of set theory, interactions between biotic ( B ), abiotic ( A ), and movement‐related ( M ) factors in the geographical space can be hypothesized with BAM diagrams and tested using ecological niche models (ENMs) to estimate A and B areas. The main aim of our survey was to evaluate the interactions between abiotic (climatic) and biotic (host availability) factors in geographical space for exotic symbionts (i.e., non‐free‐living species), using ENM techniques combined with a BAM framework and using exotic Entocytheridae (Ostracoda) found in Europe as model organisms. We carried out an extensive survey to evaluate the distribution of entocytherids hosted by crayfish in Europe by checking 94 European localities and 12 crayfish species. Both exotic entocytherid species found, Ankylocythere sinuosa and Uncinocythere occidentalis, were widely distributed in W Europe living on the exotic crayfish species Procambarus clarkii and Pacifastacus leniusculus, respectively. No entocytherids were observed in the remaining crayfish species. The suitable area for A. sinuosa was mainly restricted by its own limitations to minimum temperatures in W and N Europe and precipitation seasonality in circum‐Mediterranean areas. Uncinocythere occidentalis was mostly restricted by host availability in circum‐Mediterranean regions due to limitations of P. leniusculus to higher precipitation seasonality and maximum temperatures. The combination of ENMs with set theory allows studying the invasive biology of symbionts and provides clues about biogeographic barriers due to abiotic or biotic factors limiting the expansion of the symbiont in different regions of the invasive range. The relative importance of abiotic and biotic factors on geographical space can then be assessed and applied in conservation plans. This approach can also be implemented in other systems where the target species is closely interacting with other taxa. Abstract : We study the effects of biotic interactions on the predicted distribution of non‐free‐living alien species. We combine an ecological niche modeling (ENM) approach with the theoretical framework of set theory, by evaluating the potential distribution area of the model organisms, that is, Entocytheridae Ostracoda, and their dependence on their crayfish hosts' distribution. We found that the potential distribution of some symbiont species is constrained by both biotic (host presence) and abiotic (climatic) factors, but the expansion of others might be mostly limited just by the host presence.